(untitled) (Agro-Science Letters, 2026)
Projections suggest that nearly three-quarters of Himalayan glaciers will have retreated substantially by 2035. Additionally, a reduction in precipitation of approximately 10% is anticipated in Uttar Pradesh, India by 2050, potentially diminishing river drainage by 17%. Freshwater reserves are being depleted at an alarming rate, while expanding global populations and food requirements are eroding agricultural productivity worldwide. How well agriculture adapts to climate change will largely determine the future availability of food globally. India faces mounting challenges, including increasingly frequent droughts, intense flooding events, erratic monsoon patterns, and declining crop production linked to global climate change. Urbanization, rapid industrialization, and growing demands for irrigation water are placing extraordinary pressure on existing water resources. Land degradation is directly linked to rising global temperatures, with roughly 130 million hectares (mha) of Indian land showing various degrees of deterioration — encompassing 32.8 mha affected by water erosion, 10.8 mha by wind erosion, 8.5 mha by desertification, and a further 8.5 mha by waterlogging. This study identifies practical and cost-effective approaches to safeguarding food and water security under a changing climate, while recommending robust adaptation and mitigation strategies to reduce climate change impacts on irrigation and water resource systems.